2020
DOI: 10.1111/andr.12947
|View full text |Cite
|
Sign up to set email alerts
|

Male factor infertility trends throughout the last 10 years: Report from a tertiary‐referral academic andrology centre

Abstract: Background Trends of male factor causes of couples' infertility over time have been poorly investigated. Objective We investigated trends in the causes of pure male factor infertility (MFI) throughout the last 10 years in a tertiary‐referral academic andrology center. Material and Methods Baseline characteristics at first presentation from a cohort of 1647 consecutive male factor infertility patients belonging to primary infertile couples between 2008 and 2018 have been comprehensively collected over time. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…34 This may also explain why semen analysis alone is insufficient in predicting success when the couple is planning to undergo ART. Second, it is also known that the spectrum of potential causes of MFI has changed over time, 37 with an ever more growing number of men with more severe cases and many more unexplained or idiopathic cases for which at least a basic andrological consultation should be considered. Third, the incorrect timing of assessment, i.e., after ART, cannot only delay the couple's fertility management but may also not be cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…34 This may also explain why semen analysis alone is insufficient in predicting success when the couple is planning to undergo ART. Second, it is also known that the spectrum of potential causes of MFI has changed over time, 37 with an ever more growing number of men with more severe cases and many more unexplained or idiopathic cases for which at least a basic andrological consultation should be considered. Third, the incorrect timing of assessment, i.e., after ART, cannot only delay the couple's fertility management but may also not be cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have allowed us to understand the relationship between obesogens and weight gain better. One of the first studies demonstrated that tributyltin (TBT), a human-made chemical introduced into the environment mainly due to its widespread use as an antifouling agent in ships and other submerged structures, acts as a nanomolar-affinity ligand for PPARγ and its heterodimeric partner, 9-cis retinoic acid receptor (RXR) [7,20,55,56]. TBT is considered the obesogen model and belongs to the organotins which comprises of several families sharing structural similarities [57,58] (including e.g., butyltins, phenyltins and octyltins), being used in diverse applications including the aforementioned biocidal activities, in the production of polyurethane foams and silicones, and in the stabilization of plastics [59].…”
Section: Endocrine Disruptors As Obesogens: Evidence From Basic and C...mentioning
confidence: 99%
“…In the last decades, male fertility has decreased significantly. Today, 15% of the population is infertile, and one in seven couples is infertile at reproductive age [20]. About 50% of the cases are due to the male factor, and in many of them, it occurs due to idiopathic infertility [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A male factor contributes to up to 50% of cases of couples experiencing infertility 2 . Some modifiable factors have been associated with male factor infertility (MFI), such as diet, obesity, smoking habits, alcohol abuse, and physical exercise 3,4 . Recreational drug use has also been associated with a reduced fertility in up to 4.1% of overall infertile male cases 5 .…”
Section: Introductionmentioning
confidence: 99%